A1.17 A novel role for CD248 in controlling the differentiation of follicular dendritic cells (FDCs) following immune challenge. (13th February 2015) - Steinthal, N; Naylor, A; Nayar, S; Desanti, G; Toellner, K; Marshall, J; Fitzpatrick, M; Caamaño, J; Withers, D; Buckley, CD; Barone, C
Abstract : Background and objectives: Follicular dendritic cells (FDCs) are a stromal cell population located within the germinal centre and responsible for antigen presentation and the process of B cell affinity maturation. Although FDC function is well established, the origin and differentiation of these cells is still debated. A recent publication (Jarjour et al . JEM 2014) used multicolour fate mapping techniques to show that lymph node FDC in inflamed lymph nodes derive from marginal reticular cells (MRC), a population of stromal cells that is found underneath the lymph node subcapsular sinus. Contrasting evidence suggests that in the spleen, FDC derive from ubiquitous perivascular precursors (Krautler et al . Cell 2012). The discrepancies in these data could indicate that FDC arise from different precursors, depending on anatomical locations and stimulus. CD248 (also known as tumour endothelial marker-1 or endosialin) is a well-known, pericyte associated, stromal cell marker whose expression is significantly increased in lymph nodes and spleen following immunisation. CD248 is also upregulated in a number of disease states, including in rheumatoid arthritis. In a series of preliminary experiments, we have identified expression of CD248 within the B cell follicles, in the FDC rich area of repetitively immunised cervical lymph nodes. Materials and methods: We have immunised CD248 knockout (KO) mice i.p or in the paw pad with the hapten NP-CGG, following an established immunisation protocol that allows tracking of the antigen-specific B cell responses. We analysed the efficiency of the germinal centre response using confocal microscopy, flow cytometry and qPCR, as well as ELISAs to quantify the production of antigen-specific antibodies. Results: We present evidence that CD248 plays a role in the formation of FDC networks following immunisation. FDC networks in CD248KO mice lack the normal reticular, dendrite-like structure, despite showing only partial reduction in size. These defective networks associate with a reduction in the ability of CD248KO mice to mount a specific IgG response, implicating CD248 in FDC-mediated control of B cell maturation and production of high affinity antibodies. In vitro CD248KO mice present a defect in mesenchymal stromal cell differentiation toward a lymphoid like phenotype suggesting that CD248 is critical for lymphoid stromal cell formation. Conclusions: This data establishes CD248 + pericytes as potential precursors of FDCs. The anatomical location of CD248 + cells within the lymph node; adjacent to the nascent FDCs, identifies CD248 as a candidate for regulation of FDC function in physiological and pathological conditions. Ectopic formation of FDC in chronic autoimmune diseases such as Rheumatoid Arthritis and Sjogren's syndrome is known to associate with disease progression and worse outcome; targeting CD248 in these conditions could represent a novel and valid therapeutic approach. References: Jarjour M, Jorquera A, Mondor I, Wienert S, Narang P, Coles MC, Klauschen F, Bajénoff M. Fate mapping reveals origin and dynamics of lymph node follicular dendritic cells. J Exp Med 2014; 211 (6):1109–22. Krautler NJ, Kana V, Kranich J, Tian Y, Perera D, Lemm D, Schwarz P, Armulik A, Browning JL, Tallquist M, Buch T, Oliveira-Martins JB, Zhu C, Hermann M, Wagner U, Brink R, Heikenwalder M, Aguzzi A. Follicular dendritic cells emerge from ubiquitous perivascular precursors. Cell 2012; 150 (1):194–206.